Evaluation of brain CT scan, sonography and EEG findings in neonates with seizure - Mussavi, Mirhadi; Khanzadeh, Shokoufeh; Sadeghvand, Shahram; Hasanpour, Eslam; Akbari , Morteza; Nasiri, Shahram; Valaei , Fateme (Iranian Journal of Child Neurology, 2022)
Abstract Objectives This study aimed to determine the frequency of different types, causes, and abnormal findings of brain computed tomography scan (CT scan) and ultrasonography (US) and multichannel- electroencephalography (EEG) in neonates with seizure. The ability of brain CT scan was also compared with US in terms of detecting the underlying causes of neonatal seizures. Materials & Methods In this cross-sectional retrospective study, the medical records of 90 neonates younger than 28 days with the definite diagnosis of seizure were reviewed. The ability of brain CT scan was also compared with US in terms of detecting the underlying causes of neonatal seizures. Results Totally, 90 newborns (M: F = 1.5:1) with mean age of 63.11 ± 32.8 days were enrolled. 35.5% of newborns were born before the 37th week of pregnancy. In this study, 45.6% of EEG findings, 22% of brain CT scan findings, and 12.5% of US findings were abnormal. The automatisms (38.9%) and benign idiopathic neonatal seizure (70.7%) were the most common seizure type and cause respectively. The hypoxic Ischemic encephalopathy was the most common abnormal finding (30%) in brain CT scan. Conclusions Given the accuracy of EEG in detection of brain pathologies, where available, all neonatal seizures should be initially confirmed using EEG. Radiologic investigations (CT scan, US) off the head/ craniumshould be done to detect the cause of neonatal seizure. The capacity of brain CT scan to detect underlying causes of neonatal seizures is more than US